Linear Energy Transfer (LET) dependence of graphene oxide dosimeter for different ionizing radiations. (September 2022) - Torrisi, L.; Silipigni, L.; Cutroneo, M.; Proverbio, E.; Torrisi, A.
Abstract: The graphene oxide (GO) reduction by ionizing radiation is proportional to the absorbed dose due to the energy release which produces ionizations, deexcitations, chemical bonding breaking, radical formation and recombination, oxygen functional groups and water desorption. Thanks to this, GO can be employed as a dosimeter whose dose can be measured using different analysis techniques, such as Raman spectroscopy, X-ray diffraction (XRD) and Energy Dispersive X-ray (EDX) analysis based on the characteristic X-ray emission, X-ray photoelectron spectroscopy (XPS). To evaluate the GO reduction as a function of the Linear Energy Transfer (LET) of the used radiation, measurements have been performed with XPS and EDX to deduce the C/O atomic ratio versus the X-rays, electron and ion beam energy loss. Results indicate that a linear dependence on LET occurs, as will be presented and discussed. Highlights: GO foil can be used as dosimeter of ionizing radiation. The absorbed energy is converted in level of reduction of rGO. The dosimeter can be readout using the C/O atomic ratio by EDX and XPS analysis. The C/O ratio growths with the radiation LET.